Implementasi Zero Foodwaste Sebagai Upaya Pengelolaan Foodloss dan Food Waste pada Restoran Gardenia Sintesa Peninsula Hotel Manado - Sefania Christy Rimbing; Mirjam P. Tenda; Benny Irwan Towoliu (Yayasan Literasi Sains Indonesia, 2024)
Indonesia's food waste generation is the second largest in the world after Saudi Arabia. Food waste generation in Indonesia is estimated at 300 kilograms per person per year, while in Saudi Arabia it is 427 kilograms per person per year (Luna, & Suryana, 2022). Hotel, restaurant, catering, and household waste contribute to this waste. This research was conducted to determine the importance of awareness and understanding by restaurants as one of the contributors to food waste in Indonesia related to the issue of food waste. The approach model applied is descriptive qualitative. Data is presented in descriptive form, with this approach focusing on in-depth explanation and description of the phenomenon under study. The results showed that the main factors causing food waste at Peninsula Manado hotel were inaccuracy in organising buffet set-up, and negligence from consumers who could not manage their portions properly. The implication of this research is the need to have a special management system from the hotel in reducing food loss and food waste.